2020
DOI: 10.1080/20008686.2020.1711576
|View full text |Cite
|
Sign up to set email alerts
|

The extent and structure of pig rearing system in urban and peri-urban areas of Guwahati

Abstract: Livestock is common in Indian cities and contribute to food security as well as livelihoods. Urban livestock keeping has been neglected, and in India, little is known about the topic. Therefore, urban and peri-urban pig farms of Guwahati, Assam, India, were surveyed in order to understand more about the pig rearing systems and risks of diseases. A total of 34 urban and 66 peri-urbanpig farms were selected randomly. All reared cross-bred pigs. Free-range pig rearing was common in both urban (58.8%) and peri-urb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Based on a pilot survey and retrospective data on the availability of poultry in urban and peri-urban farms of Guwahati, the area of study was identified. Urban farms were defined as within the official city boundaries and peri-urban as within 10 km of the official city boundaries of Guwahati, the capital city of Assam (20). All villages in that circle were mapped and poultry farms identified.…”
Section: Selection Of Study Area and Location Of Poultry Farmsmentioning
confidence: 99%
“…Based on a pilot survey and retrospective data on the availability of poultry in urban and peri-urban farms of Guwahati, the area of study was identified. Urban farms were defined as within the official city boundaries and peri-urban as within 10 km of the official city boundaries of Guwahati, the capital city of Assam (20). All villages in that circle were mapped and poultry farms identified.…”
Section: Selection Of Study Area and Location Of Poultry Farmsmentioning
confidence: 99%
“…Therefore, it is obvious that highly infectious diseases like ASF can easily spread at the local level associated with free-range pig production, local pig movements, and lack of basic biosecurity measures among the pig owners. Commercial pig farms involved in high scale pig production in India are limited and can be found in urban and peri-urban areas where agricultural and market opportunities are available [ 48 ]. The risks of transmission of ASFV associated with the pig farming practice in Indian settings are described in Figure 2 .…”
Section: Risk Identification and Assessment Of Asfmentioning
confidence: 99%
“…Therefore, it is obvious that highly infectious diseases like ASF can easily spread at local level associated with free-range pig production, local pig movements and lack of basic biosecurity measures among the pig owners. Commercial pig-farms involved in high scale pig production in India are limited and can be found in urban and per-urban areas where agricultural and market opportunities are available (Mohakud et al, 2020). The risks of transmission of ASFV associated with the pig farming practice in Indian settings are described in Figure 1.…”
Section: Farming Practicementioning
confidence: 99%